2011
DOI: 10.1111/j.1443-1661.2011.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Does a Fitted Abdominal Corset Makes Colonoscopy More Tolerable?

Abstract: Our data confirm the usefulness of the abdominal corset in decreasing the degree of patient pain and it makes colonoscopy easier and quicker with less manipulation, so we propose using a fitted abdominal corset during routine colonoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…In a more recent Turkish study, 216 patients undergoing colonoscopy were randomized to receive either an “abdominal corset” or a conventional procedure. 23 The investigators reported reduced CIT in the intervention arm (7.9 minutes vs. 11.4 minutes, p=0.001) as well as decreased frequency of ancillary maneuvers. Additionally, patient pain scores were significantly reduced in the corset arm.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a more recent Turkish study, 216 patients undergoing colonoscopy were randomized to receive either an “abdominal corset” or a conventional procedure. 23 The investigators reported reduced CIT in the intervention arm (7.9 minutes vs. 11.4 minutes, p=0.001) as well as decreased frequency of ancillary maneuvers. Additionally, patient pain scores were significantly reduced in the corset arm.…”
Section: Discussionmentioning
confidence: 93%
“…23, 24 In a randomized, unblinded Japanese study of 212 patients, the use of an “abdominal bandage” was found to reduce patient-reported pain at a statistically significant level (p=0.03). 24 There was, however, no significant difference in cecal intubation rate between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Extra difficulty is added when changing the position of a sedated obese patient. A recent study in which abdominal compression obtained with a fitted corset facilitates colonoscopy reported that extra abdominal compression and a change of position was used less frequently in the study subjects accompanied by less procedural pain [21]. In contrast, no definite data are available on the effect of a change from standard left lateral decubitus to prone position in facilitating colonoscopy in obese patients.…”
mentioning
confidence: 88%
“…V jiné práci bandáž na úspěšnost totálních koloskopií vliv neměla, zato snížila bolestivost vyšetření [11]. V poslední studii bandáž zlepšila jak toleranci vyšetření, tak intubační časy a vyšetření vyžadovalo méně manipulací s pacientem [12].…”
Section: Randomizace Výpočet Velikosti Souboru a Statistická Hodnoceníunclassified